HOW TO AVOID PLAGIARISM? - Xolikova, D; Asrorova, Nafisa (INTERNATIONAL CONFERENCES, 2023)
Plagiarism is a form of dishonesty and can have serious consequences such as failure in a subject or even expulsion from a course. While there are cases of deliberate plagiarism or cheating, most cases of student plagiarism are the result of ignorance, carelessness or a lack of advanced writing skills. That’s where this thesis can help. It will help to understand what plagiarism is and to recognise examples. More importantly, the thesis focuses on strategies for avoiding plagiarism and provides valuable techniques to ensure acknowledge sources and integrate quotations appropriately in writing.